KONTRIBUSI PENEMPATAN TERHADAP MOTIVASI KERJA PEGAWAI DI DINAS PENDIDIKAN KOTA PADANG - Eni Desfitri (Ensiklopedia Social Review, 2021)
This study aims to explain the contribution of placement to employee work motivation at the Padang City Education Office. The method used in this study is a quantitative research method of ex post facto research that will describe the contribution of placement to employee motivation at the Padang City Education Office. This population involved 51 samples from a total population of 121 people, with a stratified proportional random sampling technique with education level and years of service. Data collection techniques used questionnaires, and analyzed by statistical correlation and regression techniques. The results of data processing and analysis showed that the placement of employees contributed significantly (15%) to the work motivation of administrative employees. And it can be concluded that the placement of employees affects the work motivation of the Padang City Education Office employees.